Harmonization of Legislation in the Framework of ImplementationCyber Notary din Indonesia - Saputra, Joshua Raymond; Christiana, Darista Eny; Zahroh, Addinar Fatimatus; Irianto, Sigit (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
The writing of the law on Cyber Notary analyzes and aims at the current technological developments that will later affect the making of notarial deeds into electronic deeds but require a strong legal basis so that the deed has strong evidentiary power in accordance with applicable laws and regulations. Based on the results of research and discussion, it is known that the principle of facing a notary is stated in Article 16 paragraph (1) letter m while cyber notary is in Article 15 paragraph 3 of the UUJN. The principle of facing in the Cyber Notary concept is a consideration for utilizing electronic media via teleconference (virtual). The principle of facing virtually can be applied by considering the authority and obligations of the notary. With technology, everyone can face each other virtually. So that not only facing is interpreted conventionally but virtually using applications and still on the principle of caution so that the meaning of facing virtually can be applied in the Cyber Notary concept in Indonesia. The making of notarial deeds using the cyber notary concept has not yet obtained a legal basis so that it does not provide a guarantee of legal certainty. This legal research is included in normative legal research which is descriptive analytical in nature. The data sources used are secondary data consisting of primary legal materials, secondary legal materials. Data collection techniques by systematically collecting, reviewing and processing data originating from library materials and normative-qualitative data analysis documents.